Law No. 186 of the Year 2023 Amending Certain Provisions of the Child Law Promulgated by Law No. 12 of the Year 1996 = قانون رقم 186 لسنة 2023 بتعديل بعض أحكام قانون الطفل الصادر بالقانون رقم 12 لسنة 1996 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic